2015
DOI: 10.1039/c5qi00049a
|View full text |Cite
|
Sign up to set email alerts
|

Removal of CO2from CH4and CO2capture in the presence of H2O vapour in NOTT-401

Abstract: From a binary equimolar gas-mixture of CO 2 and CH 4 , NOTT-401 exhibits CO 2 separation from CH 4 . By kinetic uptake experiments, NOTT-401 shows a maximum of 1.47 wt% CO 2 capture at 30°C and a significant 7-fold increase (∼9.90 wt%) in CO 2 capture under 40% relative humidity. † Electronic supplementary information (ESI) available: TGA data, PXRDP data, FTIR data, polynomial regressions and kinetic uptake experiments. See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Current synthetic approaches to further increase sorption selectivity towards carbon monoxide include the incorporation of open metal sites that can enhance molecular sorption, and by functionalizing the organic linker with the Lewis basic groups (e.g., amines and alcohols) [5]. Very recently, thorough investigations were also made to enhance the CO 2 capture of MOFs by using the synergistic effects caused by pre-confining small amounts of polar molecules in their pores [6][7][8]. In this regard, we previously showed that the confinement of small amounts of H 2 O in a series of MOFs (functionalized with hydroxo functional groups, µ 2 -OH) steadily resulted in improved CO 2 capture properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Current synthetic approaches to further increase sorption selectivity towards carbon monoxide include the incorporation of open metal sites that can enhance molecular sorption, and by functionalizing the organic linker with the Lewis basic groups (e.g., amines and alcohols) [5]. Very recently, thorough investigations were also made to enhance the CO 2 capture of MOFs by using the synergistic effects caused by pre-confining small amounts of polar molecules in their pores [6][7][8]. In this regard, we previously showed that the confinement of small amounts of H 2 O in a series of MOFs (functionalized with hydroxo functional groups, µ 2 -OH) steadily resulted in improved CO 2 capture properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers (CPs) are a type of crystalline material composed of metal ions or clusters connected by organic linkers (Zhou et al, 2012). Recently, CPs have shown their usefulness in a wide variety of applications, including catalysis (Guo et al, 2019;Xu et al, 2019), gas storage/separation (Islamoglu et al, 2017;Lara-García et al, 2015), magnetism (Sorace et al, 2011) and luminescence sensing (Xu et al, 2017;Yang et al, 2019). However, a large number of CPs have been synthesized using transition and main group metal ions based on organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Water molecules can disrupt coordination bonds between the organic ligands and the metal centres, resulting in the disintegration of the MOF structure. Increasingly, however, water-stable MOFs are being reported including examples such as UiO-66, MIL-101, NOTT-400 and NOTT-401 [20][21][22].…”
Section: Introductionmentioning
confidence: 99%